(3GdJMcje aj GdUfGYI GdeGdjI ddeDSSGJ GdGSJKeGQjI GdESdGejI Hjf Gdabg GdESdGej hGdbGfhf GdfehPLj (B((3GdjhfSJQGd(B) /s - (3YHGOj, ShfG YeQ Ydjs; (3GdHGR, YHGS CMeO eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdfaGFS ddfTQ hGdJhRjY,s, 2013)
(3aj GdbVGA GdTQYj(B.s
(3GdCUd CWQhMI OcJhQGg(B-(3GdLGeYI GdCQOfjI, cdjI GdOQGSGJ GdYdjG(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3UaMI (B335-345.s
(3eLdO SdhaGf(B.s
Keywords: (3GdYbhO GdJLGQjI (B((3bGfhf Ohdj(B)s; (3GdYbhO GdJLGQjI (B((3abg ESdGej(B)s